Youths’ Facial Appearance Distinguishes Leaders From Followers in Group-Perpetrated Criminal Offenses and Is Associated With Sentencing Outcomes - Sutherland, Jessica E. (Criminal justice and behavior, 2020)
Group-perpetrated crime often involves leaders and followers, but it is not currently understood how peer groups form around leaders during a criminal incident. Impression formation research has shown that specific facial cues are associated with leadership and perceptions of leadership. We extend this research to leadership among group-perpetrated youth crime and examine its role in downstream sentencing outcomes. Study 1 revealed that leaders of groups may be perceived as more dominant than their followers. In Study 2, participants were tasked with selecting the leaders from their groups and were more likely to (correctly) select targets perceived as more dominant but also (incorrectly) select targets perceived as more Trustworthy. In Study 3, we examined whether facial impressions were associated with downstream sentencing outcomes. Perceptions of Trustworthiness were associated with reduced sentencing, but dominance was unrelated. The results underscore the role that facial appearance plays in group formation and sentencing among youth.